Concurrent central diabetes insipidus and cerebral salt wasting disease in a post-operative case of craniopharyngioma: a case report - Patel Zeeshan Jameel; Sham Lohiya; Keta Vagha; Tauheed Ahmed; Divya Pujari; Jayant Vagha; Ashish Varma (BMC, 2021)
Abstract Background Water and electrolyte disorders commonly encountered in children post-surgery involving hypothalamus and posterior pituitary, are central diabetes insipidus, syndrome of inappropriate secretion of anti-diuretic hormone and cerebral salt wasting disease. Delayed diagnosis and inadequate management of such cases may lead to worsened neurological outcomes with a high mortality rate. Case presentation Here we report the case of a 7-year-old girl who underwent surgical resection of a craniopharyngioma, following which she initially developed central diabetes insipidus. However, later on in the course of her illness she developed symptomatic hyponatremia with natriuresis which was diagnosed to be due to cerebral salt wasting disease. This combination of central diabetes insipidus and cerebral salt wasting syndrome is a rare occurrence and poses a diagnostic challenge. Diagnosis and management can be even more difficult when these conditions precede or coexist with each other. Conclusion In such cases development of hyponatremia should always prompt consideration of unusual causes like cerebral salt wasting disease in addition to the classically described syndrome of inappropriate secretion of anti-diuretic hormone. Hence, a thorough knowledge of these disorders along with intensive monitoring of fluid and sodium status is critical for timely diagnosis and management of these patients.